MNAT1 is overexpressed in colorectal cancer and mediates p53 ubiquitin-degradation to promote colorectal cancer malignance - Shan Zhou; Jinping Lu; Yuejin Li; Chan Chen; Yongqiang Cai; Gongjun Tan; Zhengke Peng; Zhenlin Zhang; Zigang Dong; Tiebang Kang; Faqing Tang (Journal of Experimental & Clinical Cancer Research, 2018)
Abstract Background MNAT1 (menage a trois 1, MAT1), a cyclin-dependent kinase-activating kinase (CAK) complex, high expresses in various cancers and is involved in cancer pathogenesis. However, mechanisms underlying its regulation in carcinogenesis are unclear. Methods The tissue microarray of colorectal cancer (CRC) was used to evaluate MNAT1 expressions in CRC tissues using immunohistochemistry, CRC cell lines were also detected MNAT1 expression using Western-blotting. MNAT1 and shMNAT1 vectors were constructed, and transfected into CRC cells. Cell growths of the transfected cells were observed using MTT and colony formation. The affects of MNAT1 on p53 expression were analyzed using Western-blotting and Real-time PCR. Immunoprecipitation assay was used to analyze the interaction p53 and MNAT1, and Western-blotting was used to test the effects of MNAT1 on p53 downstream molecules. The apoptosis of CRC cells with MNAT1 or shMNAT1 were analyzed using flow cytometry. BABL/c athymic nude mice were used to observe the effect of MNAT1 on CRC cell growth in vivo. Results MNAT1 was found to be overexpressed in CRC tissues and cells, and MNAT1 expressions in CRC tissue samples were associated with CRC carcinogenesis and poor patient outcomes. MNAT1-knockin increased CRC cell growth and colony formation, and MNAT1-knockdown dramatically decreased cell motility and invasion. MNAT1 physically interacted with p53, MNAT1 also increased the interaction of MDM2 with p53. Strikingly, MNAT1 mediated p53 ubiquitin-degradation. MNAT1 shortened p53 half-life, and ectopic MNAT1 expression decreased p53 protein stability. Moreover, MNAT1 induced RAD51 and reduced p21, cleaved-caspase3, cleaved-PARP and BAX expression. MNAT1 inhibited CRC cell apoptosis. shMANT1 decreased tumor growths in nude mice following p53 increase. Conclusion MNAT1 binds to p53, mediates p53 ubiquitin-degradation through MDM2, increases cell growth and decreases cell apoptosis, and finally promotes CRC malignance. MNAT1 binding to p53 and mediating p53 ubiquitin-degradation axis represents a novel molecular joint in the p53 pathway.